TINJAUAN INTERAKSI OBAT DALAM TERAPI BRONKHITIS PADA PEDIATRI DI INSTALASI RAWAT JALAN RUMAH SAKIT UMUM DAERAH CILACAP - Kusuma, Anjar Mahardian; Novica, Tyas Adhyati (Sainteks, 2012)
Bronchitis is a kind of infection which comes from one or more infections that happens in bronchus and it’s caused by many factors. The infection may come from bacteria, allergy, etc. it needs much more medicine for bronchitis medical therapy and it enlarges the possibility for Drug Related Problems (DRPs) to happen. This study is aimed to find out Potential Drug Related Problems on pediatric bronchitis therapy in Rumah Sakit Umum Daerah (RSUD) Cilacap especially drugs interaction. Identification of Potential DRPs adverse drugs reactions (ADR) or drugs interaction. It is a descriptive research that uses data collecting method retrospectively. The research resource is patient medical record. Data analysis is done by comparing the record with releven books (Drug Interaction Fact and Stockley;s Drugs interaction). The research result shows that DRPs happen ADR or drug interaction is 20% from 140 bronchitis cases. based on the result,it can be concluded that there is Potential DRPs on pediatric bronchitis therapy in RSUD Cilacap. It’s Esspesially adverse drugs reactions (ADR) or drugs interaction Keywords: Pediatric, Bronchitis Therapy, Potential DRPs, RSUD Cilacap, Drugs Interaction, Adverse Drugs Reaction